2019
DOI: 10.1080/24748668.2019.1705643
|View full text |Cite
|
Sign up to set email alerts
|

Examining the key performance indicators of all-star players and winning teams in elite futsal

Abstract: Purpose: to identify the key performance indicators that discriminate all-star from non-all-star players; and to differentiate winning from drawing/losing teams during the Euro Cup 2018 Futsal (Slovenia). Methods: the sample consisted of all matches (n = 20) played by 12 teams (87 players). Differences between both players and teams were calculated using the Mann-Whitney U and student-t tests and the binary logistic regression (assessing the relationship between all-star players or winning teams and several ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…As such, the recent findings by Portuguese and Spanish authors ( Santos et al, 2020 ) who investigated key performance indicators that discriminated all-star from non-all-star players during the Euro Cup 2018 Futsal (Slovenia) confirm the relevance of differentiating physical capacities (i.e., kicking speed, futsal-specific agility, and reactive strength) between starters and non-starters in this study. In brief, those authors found that all-star players had greater numbers for key pass accuracy and assists and achieved a higher number of goals with a better rate of shots on target during the matches.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…As such, the recent findings by Portuguese and Spanish authors ( Santos et al, 2020 ) who investigated key performance indicators that discriminated all-star from non-all-star players during the Euro Cup 2018 Futsal (Slovenia) confirm the relevance of differentiating physical capacities (i.e., kicking speed, futsal-specific agility, and reactive strength) between starters and non-starters in this study. In brief, those authors found that all-star players had greater numbers for key pass accuracy and assists and achieved a higher number of goals with a better rate of shots on target during the matches.…”
Section: Discussionsupporting
confidence: 82%
“…This observation can be explained by the adopted sports-specific movement (i.e., running, acceleration, and deceleration) technique that includes lowering of the center of gravity, shorter strides, a sideways leaning posture toward the intended direction, and proper foot placement ( Haugen et al, 2014 ). All of these factors together allow the lower-body muscles to apply sufficient and optimal lateral force to the ground, which in turn enables players to maintain balance and efficiently perform futsal-specific tasks that include many rapid changes of direction both with and without the ball ( Haugen et al, 2014 ; Caetano et al, 2015 ; Santos et al, 2020 ). These observations together indicate that differences between the studied performance-levels are more closely related to (i) specific futsal skills and (ii) reactive strength, which enables players to efficiently execute futsal-specific movements, as already suggested ( Sekulic et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pass is a collective action that requires tactical action adjusted to the context, based on the spatiotemporal relationship with the teammates and the projection of the ball into that space in view of the time available with the appropriate biomechanics 3 . However, in addition to the biomechanical aspects, the accuracy of the pass is essential to enhance relations with teammates considering the position of opponents [2][3][4] . In fact, in unpredictable sports, right and wrong depend on the context played at that time and the objective achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding that, in order to promote significant advances and unbalances, it is necessary to overcome defensive lines to cause defensive readjustments and even space-time unbalances in defense in relation to the attack, and according to Santos et al 4 , which directly contributes to a finalization situation, thus facilitating a goal-scoring opportunity. This type of pass is known as the imbalance pass (a pass that leaves the defense partially or totally destabilized/unbalanced, which contribute directly to a finishing situation, numerical advantage in the construction process, spatial advantage in a 1x1 situation, and may facilitate the chance of scoring a goal), being an indicator of the performance of elite athletes 4 .…”
Section: Introductionmentioning
confidence: 99%